The magmatic evolution of igneous intrusions in Grønsteinfjellet-Botneheia, Svalbard - Malinen, Lauri (Helsingin yliopisto, 2024)
The Early Cretaceous igneous rocks in the circum-Arctic, collectively referred to as the High Arctic Large Igneous Province, are predominantly manifested on Svalbard as dolerite intrusions, classified as the Diabasodden Suite. The well-exposed intrusions in the Grønsteinfjellet- Botneheia study area, Svalbard, provide a window to a magmatic plumbing system, which has not been previously thoroughly studied. Samples collected in 2022 and 2023 were analysed for whole-rock major and trace element geochemistry. Additionally, two thin sections were studied petrographically and analysed for mineral chemistry. Geochemical data were used to model fractional crystallization, calculate primary melt composition and depth of crystallization for clinopyroxene. Stratigraphical maps and available elevation data were used to estimate the final emplacement depths of the intrusions. The geochemistry of the intrusions represents well-evolved tholeiitic basalts. The primary melt composition, with a minimum MgO content of 13.8 wt.%, suggests 45 mol% fractional crystallization before reaching a composition similar to the most primitive sample. Whole-rock major and trace element data, supported by the modelled fractional crystallization, indicate that fractional crystallization has been the primary magmatic differentiation process, while complex zoning and mineral chemistry suggest additional differentiation processes, such as magma mixing. Over-enrichment of K, Rb and Ba, implies crustal contamination. The presence of amygdales and depletion of mobile elements K and Rb indicate hydrothermal alteration. Thermobarometric calculations suggest multi-stage crystallization at depths from 2.8 to 11.2 km. The final emplacement depths were estimated to range from 230 to 560 m, based on elevation differences with the coeval Helvetiafjellet Formation. These findings propose that the Grønsteinfjellet-Botneheia intrusions underwent various and extensive differentiation processes before being emplaced in a shallow environment.